(untitled) (Philological Studies, 2019)
The article represents the main characteristics of personal, demonstrative, comparative and extended coreference in a judgement, one of the most significant Slovene legalistic texts. Analysis is based on the typology of M.A.K. Halliday and R. Hasan (1976), while the research corpus consists of 30 judgements issued by Slovene civil courts of justice in the period 1997–2003. Owing to their mandatory and legislative nature, legalistic texts have to provide exactness and unequivocalness of information. These tendencies are also demonstrated in the surface textual organisation of a judgement. The realisation of personal coreference with personal pronouns as a cohesive source is hardly a special case in a judgement. To ensure the precision and unequivocalness of facts, legal professionals in most cases use repeated lexical reference instead of personal pronouns, which reduces informativity. Within the demonstrative coreference, anaphoric demonstrative pronouns mostly occur as cohesive sources, appearing autonomously only in the low level distance of the elements in the coreference tie. Otherwise, they occur as reinforced coreferential elements and function as accompanions of repeated reference, in order to emphasise the determination of reference. Comparative coreference is mostly realised with the superlative and comparative conjunction kot, while extended coreferential ties often occur in adduction of proofs, laws and provisions used by the court to give a judgement. Regarding the tendency of legalistic texts towards accuracy and unequivocalness, there are only a few cataphoric coreferential ties, namely inadducing inserts, documentation and court costs. With respect to the distance between the elements of the coreferential tie, coreferential ties in a judgementaremain textually in contact. However, owing to the frequent repetition of references and redoubled referents, this does not assure textual comprehension.